Relationship between maximal oxygen uptake, within-set fatigue and between-set recovery during resistance exercise in resistance-trained men and women - Tommy R. Lundberg; Gustav Larsson; Rasmus Alstermark; Mirko Mandić; Rodrigo Fernandez-Gonzalo (BMC, 2024)
Abstract Background The primary aim of this study was to examine the relationship between maximal oxygen update (V̇O2max) and within-set fatigue and between-set recovery during resistance exercise in men and women. Methods We examined the relationship between V̇O2max and various indices of fatigue and recovery during parallel squats (3 sets, 90 s rest, 70% of 1RM to failure) and isokinetic knee extensions (3 × 10 maximal repetitions at 60 deg/s, 45 s rest) in 28 (age 27.0 ± 3.6 years) resistance-trained subjects (14 men and 14 women). We also examined whether there were sex differences in within-set fatigue and between-set recovery. Results V̇O2max was weakly related to recovery and fatigue in both men and women (range of P-values for V̇O2max as a covariate; 0.312-0.998, range of R-values, 0.005-0.604). There were no differences between the sexes in fatigue within a set for the squat, but men showed less within-set fatigue than women in the first set of the isokinetic knee extension exercise (~ 8% torque loss difference, main effect of sex P = 0.034). Regarding recovery between sets, men showed greater relative peak power (P = 0.016) and peak torque (P = 0.034) loss between sets in both exercises, respectively, compared to women. Women also tended to complete more repetitions than men (main effect of sex, P = 0.057). Loss of peak torque between sets in knee extension was evident in both absolute and relative (%) values in men but not in women. Conclusions Our study suggests that aerobic capacity is weakly associated with within-set fatigue and between-set recovery in resistance training in both men and women. Women and men show comparable levels of within-set fatigue in the multi-joint squat, but women show more within-set fatigue during the single-joint isokinetic knee extension compared with men. In contrast, women recover better than men between sets in both exercises.